Inverse pole figure mapping of bulk crystalline grains in a polycrystalline steel plate by pulsed neutron Bragg‐dip transmission imaging. Issue 6 (11th October 2017) - Sato, Hirotaka; Shiota, Yoshinori; Morooka, Satoshi; Todaka, Yoshikazu; Adachi, Nozomu; Sadamatsu, Sunao; Oikawa, Kenichi; Harada, Masahide; Zhang, Shuoyuan; Su, Yuhua; Kamiyama, Takashi; Ohnuma, Masato; et al.
Abstract : Pulsed neutron Bragg‐dip transmission is an efficient method for determining the crystallographic direction of crystals lying parallel to the incident beam. The method can be used for crystalline grain identification with a spatial resolution higher than that achievable by neutron diffraction imaging. Abstract : A new mapping procedure for polycrystals using neutron Bragg‐dip transmission is presented. This is expected to be useful as a new materials characterization tool which can simultaneously map the crystallographic direction of grains parallel to the incident beam. The method potentially has a higher spatial resolution than neutron diffraction imaging. As a demonstration, a Bragg‐dip neutron transmission experiment was conducted at J‐PARC on beamline MLF BL10 NOBORU. A large‐grained Si–steel plate was used. Since this specimen included multiple grains along the neutron beam transmission path, it was a challenging task for existing methods to analyse the direction of the crystal lattice of each grain. A new data‐analysis method for Bragg‐dip transmission measurements was developed based on database matching. As a result, the number of grains and their crystallographic direction along the neutron transmission path have been determined.